A campus-wide Testbed Over the TV White Spaces - Chandra, Ranveer; Moscibroda, Thomas; Bahl, Victor; Murty, Rohan; Nychis, George; Wang, Xiaohui (ACM SIGMOBILE Mobile Computing and Communications Review, 2011)
We have deployed a wireless network that operates in the white spaces of the TV band spectrum and covers most of Microsoft campus in Redmond, WA. Since the campus is large (approximately 1 mile x 1 mile), there are several shuttles that move employees from one building to another. We have used the white spaces network to enable a key productivity scenario on campus - Internet connectivity in campus shuttles. We have modified one such shuttle to operate over the TV band white spaces. A white space radio in this shuttle communicates with two base stations deployed on buildings on campus. Inside the shuttle, we bridge the white space connection to Wi-Fi, so that an employee's laptop that does not have an integrated white space radio can nevertheless connect to the Internet, using Wi-Fi within the shuttle, and white spaces between the shuttle and the base stations. To the best of our knowledge, this is the first network deployed over the TV white spaces.